Major thinkers in welfare : contemporary issues in historical perspective - George, Victor (Policy Press, 2010)
This is the first book to examine the views of a number of theorists from ancient times to the 19th century on a range of welfare issues: wealth, poverty and inequality; slavery, gender issues, and the family; child rearing and education; crime and punishment; the role of government in society; the strengths and weaknesses of government provision vis-à-vis market provision. The book also looks at the values of the various theorists as well as their perception of human nature for these tend to underpin their welfare views.